Nirs Technology (Near Infrared Reflectance Spectroscopy) for Detecting Soil Fertility Case Study in Aceh Province: Review - Siti Mechram; Bambang Rahadi; Zaenal Kusuma; Soemarno (Future Science, 2021)
Assessment of soil fertility status can be done through a soil test approach, but the main problem is the difficulty of predicting the nutrient content in the soil. This requires laboratory testing and takes several times, while the nutrient requirements must be known immediately so that plants can grow ideally. In the last few decades, researchers have been trying to find alternative methods that are fast, innovative, effective, environmentally friendly, and non-destructive to predict nutrient concentrations. One of the technologies that are currently developing rapidly and has the potential to be used to detect/predict the nutrient content is near-infrared reflectance (NIR). Many studies have been conducted and reported related to the application of close-range infrastructure technology, especially for speed and soil quality. This paper discusses several reviews of research in Aceh Province related to the application of NIRS Technology to detect soil fertility. The NIR technique is an analytical technique that is fast and does not damage the sample of the material to be tested. Information on chemicals based on biological reactions after exposure to NIR radiation. Near-infrared light is available in the wavelength range up to 780 nm to 2500 nm or above visible light. When a ray coming from a light source A falls on a biological object, there will be an interaction between the object and the light. The object's location will respond in the form of reflection, absorbance and transmission. The reflection response can be in the form of direct reflection (specular reflectance) which means that light is reflected back by objects, pseudo reflection (diffuse reflectance) where light is first and then reflected. This research about NIR technology, it can solve problems, especially regarding the improvement and evaluation of soil fertility by predicting the right model to measure the nutrient content of the soil.